Consideration Through the Psychological, Social Environment, and Technology That the Younger Generation Accepts to Buy Now Pay Later - Ayunda Listy Fatia; Dahniar Dahniar; Putri Puspita Ayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study has examined the factors that affect the behavioral intentions of the younger generation in using Buy Now Pay Later (BNPL) services in Indonesia. Adopting the theoretical framework of 2 variable UTAUT performance expectations, and social influence, which has been expanded with Perceived Risk, and financial literacy on the behavioral intention of BNPL use. With a quantitative approach, primary data were collected from 247 respondents aged 18-41 years who were BNPL users, and analysis was conducted using the Partial Least Squares Structural Equation Model (PLS-SEM) method. In the results of this study, the three variables, namely financial literacy, performance expectations, and social influence, have a significant positive influence on behavioral intentions. Meanwhile, Perceived Risk showed a significant positive influence, which contradicted the initial hypothesis. In conclusion, this study shows that individuals with high levels of financial literacy are able to manage risk and remain motivated to use Pay Later. This research is expected to contribute to an academic and practical understanding of the dynamics of financial technology adoption among the young generation of Indonesia, in particular.